2022
DOI: 10.3390/healthcare10122348
|View full text |Cite
|
Sign up to set email alerts
|

Habilitation of Executive Functions in Pediatric Congenital Heart Disease Patients through LEGO®-Based Therapy: A Quasi-Experimental Study

Abstract: Congenital heart disease is defined as an abnormality in the cardiocirculatory structure or function. Various studies have shown that patients with this condition may present cognitive deficits. To compensate for this, several therapeutic strategies have been developed, among them, the LEGO® Education sets, which use the pedagogic enginery to modify cognitive function by didactic material based on mechanics and robotics principles. Accordingly, the goal of this study was to evaluate the effect of cognitive hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In recent years, ER has increased its inclusion in classrooms and in the scientific literature as a consequence of the benefits it presents. Several studies have demonstrated its positive impact on the development of skills such as computational thinking, critical thinking, problem solving, creativity, motivation, and metacognitive skills [34][35][36][37][38]. According to the scientific literature, learning via robotics means that students learn knowledge from different areas, such as science and mathematics, and biosanitary content through the use of robots [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, ER has increased its inclusion in classrooms and in the scientific literature as a consequence of the benefits it presents. Several studies have demonstrated its positive impact on the development of skills such as computational thinking, critical thinking, problem solving, creativity, motivation, and metacognitive skills [34][35][36][37][38]. According to the scientific literature, learning via robotics means that students learn knowledge from different areas, such as science and mathematics, and biosanitary content through the use of robots [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated its positive impact on the development of skills such as computational thinking, critical thinking, problem solving, creativity, motivation, and metacognitive skills [34][35][36][37][38]. According to the scientific literature, learning via robotics means that students learn knowledge from different areas, such as science and mathematics, and biosanitary content through the use of robots [38][39][40][41][42]. Despite this, there is very little scientific literature analyzing the influence of ER on improving curricular content, especially bioscience content, and existing studies usually focus on improving the knowledge and skills related to the robot itself and its handling [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%